Renovación Urbana de la Avenida la Toma en Neiva, Huila (2020)
Urban development in cities encounters a bad organization in its planning due to rapid growth in urban areas, generating a deterioration in resources and quality of the environment, so there is a need to generate a sustainable city environment with the population, being indispensable for the future. Hence the importance of implementing a system of stable and replicable urban measurement methodologies that allow for the development of a sustainable urban plan that improves the quality of life of the inhabitants and their inhabitants, guaranteeing to adapt ecological planning bases and technologies that generate in people A knowledge of alternatives in a sustainable life. This analysis demonstrates the need to integrate a focus on project progress through a system in the methodology that helps to gather information with research tools, resulting in a process in the restoration and formation of the city through a proposal urban replicable, with the objective of studying the city of Neiva specifically the sector of Avenida la Toma for being one of the environmental axes with a channeled stream. In conclusion, emphasizing the importance of promoting new alternatives in the design of a city, with an offer for the progress of a population in which it fulfills its purposes to improve the order and quality of the environment as well as the activities of the community.